2002
DOI: 10.1182/blood-2002-01-0048
|View full text |Cite
|
Sign up to set email alerts
|

A randomized multicenter comparison of bone marrow and peripheral blood in recipients of matched sibling allogeneic transplants for myeloid malignancies

Abstract: Cytokine-mobilized peripheral blood is increasingly used instead of bone marrow as the source of cells for allogeneic transplantation. Although cells lead to faster hematologic recovery, their effects on graft-versus-host disease, relapse, and survival are less certain. Between January 1996 and February 2000, 228 patients with chronic myeloid leukemia, acute myeloid leukemia, or myelodysplasia were randomized to receive either bone marrow or peripheral blood allografts from HLA-matched siblings. All patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
6
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(193 citation statements)
references
References 35 publications
(15 reference statements)
12
171
6
4
Order By: Relevance
“…Nevertheless, the incidence of grades 2-4 acute GVHD observed in the G-CSF group in this trial (49%) is clearly in line with rates (21-64%) reported in the PBPC arms of several randomized trials. [1][2][3][4][5][6][7] The lack of any grade 3-4 acute GVHD in the GM-CSF group is noteworthy given the large proportion of patients transplanted for high-risk disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the incidence of grades 2-4 acute GVHD observed in the G-CSF group in this trial (49%) is clearly in line with rates (21-64%) reported in the PBPC arms of several randomized trials. [1][2][3][4][5][6][7] The lack of any grade 3-4 acute GVHD in the GM-CSF group is noteworthy given the large proportion of patients transplanted for high-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Nevertheless, in only a minority of the randomized comparative trials did this translate into an overall survival advantage and some studies suggested the use of G-CSF mobilized PBPC was associated with a greater risk of either acute or chronic graft-versus-host disease (GVHD), or both. 6,[8][9][10] In two recent retrospective studies in patients with aplastic anemia or children with leukemia performed by the International Bone Marrow Transplant Registry, transplantation of G-CSF mobilized PBPC was associated with higher rates of GVHD.…”
Section: Csf; G-csfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a higher incidence of chronic GVHD in PBSCT compared to SCT using sBM may be more acceptable with current management strategies. 1,2,8,9,15 Moreover, based on a meta-analysis performed in 2001, PBSCT involves a slightly increased risk of acute GVHD. 16 More importantly, recent studies have found no significant difference between PBSCT and SCT using pBM in terms of engraftment, although PBSCT involved a significantly increased risk of acute and/or chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition, allogeneic G-CSF-primed bone marrow (pBM) stem cells appear to be similar to PBSCs in terms of engraftment potential. [3][4][5][6][7] Overall, allogeneic hematopoietic SCT using pBM results in more rapid engraftment with a lower incidence of chronic GVHD than SCT using PBSCs.…”
Section: Introductionmentioning
confidence: 99%